Continuous‐Flow Pd‐Catalyzed Carbonylation of Aryl Chlorides with Carbon Monoxide at Elevated Temperature and Pressure. Issue 3 (15th January 2019) - Mata, Alejandro; Hone, Christopher A.; Gutmann, Bernhard; Moens, Luc; Kappe, C. Oliver
Abstract: The development of a continuous‐flow protocol for a palladium‐catalyzed methoxycarbonylation of (hetero)aryl chlorides using carbon monoxide gas and methanol is described. (Hetero)aryl chlorides are the least expensive of the aryl halides, but are underutilized in carbonylation reactions due to their very poor reactivity. The described protocol exploits intensified conditions at elevated temperature and pressure, which are readily accessed within a continuous‐flow environment, to provide moderate to excellent product yields (11 examples) in a short 16 min residence time. The continuous‐flow protocol enables the safe and potentially scalable carbonylation of aryl chlorides using CO gas. Abstract : Continuous‐flow Pd‐catalyzed carbonylation of aryl chlorides with carbon monoxide at elevated temperature and pressure @KappeLab @RCPE @UniGraz @JanssenGlobal